Convective Drying of Turmeric Rhizome - Gagare, Santosh; Mudgal, V. D.; Champawat, P. S. (Journal of Agricultural Engineering, 2018)
Experimental trials on convective drying of turmeric (Curcuma longa L) rhizomes were conducted using factorial completely randomized design. Turmeric rhizome samples were cured for 30 min in 0.1 % solution of sodium carbonate and dried in a laboratory tray dryer at air temperatures of 50 °C, 60 °C and 70 °C with drying air velocity of 2 m.s-1. Drying air temperature was optimized on the basis of maximum retention of curcumin content, and b value of colour with minimum drying time and specific energy consumption. Optimization of drying parameters was carried out using numerical optimization technique. The optimum temperature for convective drying of turmeric rhizomes was found to be 60 °C with drying time of 29 hours.